Recent Progress in Manufacturing Techniques of Printed and Flexible Sensors: A Review - Dinesh Maddipatla; Binu B. Narakathu; Massood Atashbar (Biosensors, 2020)
This review provides an outlook on some of the significant research work done on printed and flexible sensors. Printed sensors fabricated on flexible platforms such as paper, plastic and textiles have been implemented for wearable applications in the biomedical, defense, food, and environmental industries. This review discusses the materials, characterization methods, and fabrication methods implemented for the development of the printed and flexible sensors. The applications, challenges faced and future opportunities for the printed and flexible sensors are also presented in this review.